Selective secure error correction on SPIHT coefficients for pervasive wireless visual network. (30th May 2013) - Ong, Jia Jan; Ang, Li–Minn; Seng, Kah Phooi
This paper presents a secure error correction architecture with data compression using SPIHT algorithm for implementation in the wireless visual network (WVN). By using Cauchy Reed Solomon (CRS) coding scheme, the mapping bits produced from the SPIHT algorithm will be protected from errors and any adversary attack during the wireless transmission. In order to meet the hardware constraints of WVN, the CRS architecture is developed based on a very low complexity structure employing a minimal instruction set computing (MISC) architecture. For this, a particular configuration of the CRS MISC is chosen that has the similar key space security as provided by the Advance Encryption Standard (AES). Both SPIHT MIPS and CRS MISC architectures are implemented onto an FPGA, resulting in only 5017 slices and 82 block RAMs on the Xilinx Virtex 2, which demonstrate the feasibility for implementation in low complexity sensor nodes.